유채 잡종 1세대의 소포자 배양에 의한 배가반수체 집단 선발 및 지방산 조성 분석 - 이지은; 박주현; 김광수; 안다희; 차영록; Lee, Ji Eun; Park, Ju Hyun; Kim, Kwang Soo; An, Da Hee; Cha, Young Lok (Journal of plant biotechnology, 2022)
Brassica napus, an oil crop that produces rapeseed oil, is an allotetraploid (AACC, 2n = 38) produced by natural hybridization between B. rapa and B. oleracea. In this study, microspore was cultured using the F1 developed from a cross between 'EMS26' line with high oleic acid content and 'J8634-B-30' lines. The flower bud size showing the nuclear development at the late uninucleate and binucleate stage with high embryogenesis rate was 2.6 ~ 3.5 mm. Microspores were cultured using only this size and after then most microspore embryo developed into secondary embryos and then regeneration plants obtained from the developed multilobe. The analysis of the ploidy of the plants revealed that 66.7% and 27.8% of the total lines were tetraploids and octoploids, respectively. The sizes of stomatal cells in tetraploids, octoploids, and diploids were 25.5, 35.6, and 19.9 ㎛, respectively, indicating that ploidy level was positively correlated with cell size. Furthermore, 62 tetraploid doubled haploid (DH) lines were selected. The average oleic acid (C18:1) and linolenic acid (C18:3) concentrations of DH were 72.3% and 6.2%, respectively. Oleic acid and linolenic acid concentrations exceeded the two parental values in 5 and 14 DH lines, respectively, suggesting that these two fatty acids had transgressive segregation. Therefore, the DH population can be utilized for the biosynthesis of unsaturated fatty acids in rapeseed and related genes. It can also be used as a breeding material for varieties with high oleic acid concentrations. 유채(Brassica napus)는 배추와 양배추의 자연 교잡에 의해 만들어진 이질사배체 작물(AACC, 2n = 38)로, 유채유를 생산하는 기름 작물이다. 본 연구에서는 올레산 함량이 높은 유채 EMS26 계통과 J8634-B-30 계통의 잡종 1세대 소포자를 이용하여 배양을 실시하였고, 재분화 식물체의 배수성을 검정하고 배가반수체 집단을 선발하여 C18 지방산 조성을 분석하였다. 먼저 꽃봉오리의 크기에 따른 소포자 발달 단계를 확인하였으며, 소포자 배 발생 효율이 높은 1핵기 말과 2핵기 발달 단계를 보이는 꽃봉오리 크기는 2.6 ~ 3.5 mm였다. 본 크기의 꽃봉오리만을 이용하여 소포자 배양을 실시하였으며, 배양 10일 후에 구형배와 심장형배가 관찰되었다. 소포자배는 캘러스를 형성하여 2차배로 발달하였으며, 이후 발달된 multilobe로부터 108 계통의 재분화 식물체를 획득하였다. 재분화된 식물체의 배수성은 4배체가 66.7% (72계통)로 다수였으며, 8배체는 27.8% (30계통), 그리고 2배체는 5.6% (6계통)로 확인되었다. 각 배수성에 따른 기공 세포의 크기는 4배체, 8배체, 2배체 각각 25.5 ㎛, 35.6 ㎛, 19.9 ㎛로 나타나, 배수성과 세포 크기는 정의 상관관계를 보였다. 이중 4배체 배가반수체 식물체 62계통을 선별하여 지방산 조성을 분석한 결과, 평균 올레산(C18:1) 함량은 72.3%, 리놀레산(C18:2) 11.8%, 리놀렌산(C18:3) 6.2%로 나타났다. 특히 올레산 함량이 가장 높은 계통은 DH22 계통으로 77.6%였으며, 리놀렌산 함량은 DH19계통에서 13.4%로 가장 높았다. 또한 모부본 보다 높은 올레산과 리놀렌산 함량을 보이는 계통은 각각 5개와 14개로 초월 분리(Transgressive segregation) 현상을 보였다. 이렇게 확보된 배가반수체 유전 집단은 유채의 불포화 지방산 생합성 기작 및 관련 유전자 탐색에 활용 가능하며, 올레산 함유량이 높은 계통들은 고품질 유채유 생산 품종 육종 소재로 활용 될 수 있을 것으로 기대된다.